Peningkatan Hasil Belajar Peserta Didik Kelas IV pada Materi Operasi Pembagian Bilangan Cacah Melalui Penggunaan Media Counting Box - Fadhila, Raoddotul; Zahrah, Riza Fatimah; Sidik, Geri Syahril (Indo-MathEdu Intellectuals Journal, 2025)
This study was motivated by the low cognitive achievement of students in mathematics, particularly in division, with 61.90% of students not meeting the Minimum Mastery Criteria. The study aims to improve the learning outcomes of fourth-grade students in understanding whole number division through the use of a concrete teaching medium, the counting box. This classroom action research was carried out in two cycles at SD Negeri Mangkubumi, Tasikmalaya, involving 21 students. Data were collected through observations and written tests. The research followed the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. The results showed a significant improvement in student learning outcomes, with the average score increasing from 65.71 in the pre-cycle to 88.81 in the first cycle and 93.10 in the second cycle. The use of the counting box media enhanced students’ understanding through concrete and visual learning experiences, which led to greater engagement and improved mastery of concepts. These findings indicate that concrete media such as the counting box can be effectively used in primary mathematics instruction to support students’ achievement in basic arithmetic operations.